Reading to learn in a foreign language : an integrated approach to foreign language instruction and assessment - Koda, Keiko, 1954-; Yamashita, Junko, (Professor) (Abingdon, Oxon ; New York, NY : Routledge, 2019)
"This book describes a theory-guided approach to Foreign Language (FL) course development, implementation, instruction and assessment. It documents the development and implementation of a theory-guided approach designed to exploit cross-linguistically sharable competencies as resources for promoting FL learning. The volume delineates the processes of (a) identifying cross-linguistically sharable competencies, (b) exploring ways of exploiting sharable competencies as resources in promoting language skills through their purposeful use for content learning, (c) implementing the instructional approach in multiple EFL classrooms, and (d) evaluating the approach by comparing learning outcomes across classrooms. It presents a solid conceptual framework that integrates theories in multiple research domains, including second language acquisition, knowledge acquisition, and language assessment. It also provides detailed descriptions of framework construction and classroom implementation - the two processes that are integral to course design and development"--
Reading to learn: why and how content-based instructional frameworks facilitate the process / William Grabe and Fredricka L. Stoller -- Integrated communication skills approach: reading to learn as a basis for language and content integration / Keiko Koda -- Fostering reading to learn skills in classrooms -- Integrating content as a way of promoting students: involvement and ownership in skill focused instruction / Junko Yamashita -- Cultivating reading to learn skills in fostering oral presentation competence as an essential tool for participating in an increasingly globalized society / Remi Murano -- Challenges for an EFL teacher and basic writers: negotiating space for change under a rigid curriculum / Kyoko Baba -- Motivating low-intermediate students to use language skills for learning and thinking about American society in project-based EFL instruction / Shingo Ichikawa -- Promoting intrinsic motivation and transcultural competence through IC skills training / Masumi Kojima -- Enhancing lexical sophistication through IC skills training in low-intermediate Chinese as a foreign language in the US / Stanley Zhang and Keiko Koda -- Developing reflective leaners in Chinese as a foreign language in the US / Sihui (Echo) Ke and Keiko Koda -- Benefits and challenges of theory-guided approaches to FL instruction / Junko Yamashita and Keiko Koda.
Includes bibliographical references and index.
ENH
Parama
Keywords: Second language acquisition; Reading